Thermochemical and kinetic studies of polymerization and other properties. - McCurdy, Keith G. (University of Ottawa (Canada), 1963)
Heat of polymerization. With the use of a Tian-Calvet microcalorimeter, the heats of polymerization of a number of monomers have been measured in aqueous emulsion systems; the emulsifying agent was cetyltrimethylammonium bromide, and initiation was by Fenton's reagent (Fe++ + H 2O2). The monomers employed were acrylic acid, methyl, ethyl and butyl acrylates, hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, methacrylic acid, and methyl, ethyl, butyl and hexyl methacrylates. The heats of polymerization lie in the range from 13 to 19 kcal per mole, the experimental standard deviation being 40 to 110 cal per mole. A steady increase was observed for acrylic acids and its CH3, C2H5 and C 4H9 esters, and for methacrylic acid and its CH3, C2H5, C4H9 C6H 13 esters. This change is attributed to a steady increase in the proportion of head to head, tail to tail polymers, leading to a decrease in steric hindrance in the polymer. Abnormally low heats observed with hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate are attributed to the solvation of the monomer, less solvation being possible in the polymer as a result of shielding. Kinetics of polymerization. The microcalorimeter has been used to obtain rates of polymerization of a number of monomers in emulsion systems. The rates with the acrylates are consistently higher than those with the methacrylates, and this is attributed to there being less steric hindrance in the acrylate polymerization. Low rates found with the monomers containing a hydroxyl groups are explained as due to solvation in the initial monomer state. In both the acrylates and methacrylates the rates go through a maximum as one goes up the series methyl: ethyl: butyl: hexyl. This is discussed in terms of inductive and steric effects. Heats of vaporization. Heats of vaporization of fourteen alcohols, having from one to five carbon atoms, have been determined in a Calvet microcalorimeter, using a special technique. The method consisted of allowing the alcohol to vaporize into a vacuum, the heat required for the vaporization being provided by passing a current through a resistance wire which was immersed in oil in a U-tube surrounded by the alcohol. The additivity scheme previously devised by Laidler for heats of formation and related properties was applied to the results, and the agreement with experiment was within a few tenth of a percent. Additivity. An empirical bond energy scheme has been derived and applied to several physico-chemical properties of several families of compounds. The scheme proposed is a modification of Tatevskii's scheme. It defines three types of C-H bonds and several types of C-C bonds depending on their multiplicity and their environment. Other functional groups (e.g. -CHO, -COH) have been considered as a group and have been treated as such. They are assigned group symbols and their contribution to the physico-chemical property is a group contribution. The scheme has been applied to alkanes, alkenes, dienes and cylic hydrocarbons for the following properties; molar volume, molar refraction, entropy of formation and heat of atomization, all at 25°C. Molar sound velocities and diamagnetic susceptibilities are two other properties treated for several families of compounds.
Keywords: Chemistry, Polymer.